Bobosharif S. answered • 03/19/18

Mathematics/Statistics Tutor

It is very similar to your other question

y=3/2x+1

y-1=3/2x

2x=3/(y-1)

x=3/(2(y-1))

So, f

^{-1}(y)=3/(2(y-1)) or f^{-1}(x)=3/(2(x-1))Shaukat K.

asked • 03/19/18Show step by step.

Follow
•
2

Add comment

More

Report

Bobosharif S. answered • 03/19/18

Mathematics/Statistics Tutor

It is very similar to your other question

y=3/2x+1

y-1=3/2x

2x=3/(y-1)

x=3/(2(y-1))

So, f^{-1}(y)=3/(2(y-1)) or f^{-1}(x)=3/(2(x-1))

Ask a question for free

Get a free answer to a quick problem.

Most questions answered within 4 hours.

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.